"Thinking about the future, what's gonna happen?"—How young people in Sweden who neither work nor study perceive life experiences in relation to health and well-being. Issue 1 (1st January 2018) - Lögdberg, Ulrika; Nilsson, Bo; Kostenius, Catrine
ABSTRACT: Purpose: The aim of this study was to explore how young people in Sweden who neither work nor study perceive life experiences in relation to health and well-being. Methods: A task-based interview technique was used and data was analysed with qualitative content analysis. Interviews were conducted with 16 participants aged 16-20 who were unemployed and not eligible for upper secondary school, or who had dropped out of school. Results: Three themes emerged from the analysis illustrating how the young people perceive their life experiences in relation to health and well-being: Struggling with hardships in the absence of caring connections, Feeling good when closely connected to others, and Being forced to question what has been taken for granted . Each theme consists of 2-3 subthemes. Conclusion: Based on the young people's narrated experiences health can be understood as: something that is created in relation to others and in relation to the social and cultural context; as something dynamic and changeable; as the ability to adapt and respond to challenges; and finally as something existing on a collective as well as an individual level. Implications for school, social services and health promotion initiatives are discussed, with an emphasis on working with young people.